Model Konseptual Pengembangan Wisata Bahari Secara Berkelanjutan di Wilayah Pesisir dan Pulau-Pulau Kecil Kota Makassar - Rosmawaty Anwar (Journal of Tourism Destination and Attraction, 2014)
Makassar City has an enermous potential on marine tourism due to its strategic location in the coastal area of Southern Sulawesi. Makassar is surrounded by several small islands, abundant marine resources and many marine tourism attraction. But the development of tourism within coastal area and small islands is showing unbalance situation. To gain proper development of marine tourism in those coastal area and small islands, an institutional approach is needed. This research suggest a conceptual model of sustainable tourism by deciding leading sector and establishing a consortium which bear management collaboration. This institution is representative of all stakeholder and responsible to optimaze coordination, cooperation and consultation within local and regional autorities, tourism industry, local communities, academic institution, non goverment organization, and mass media. It also needs to provide training on community based tourism.